The Effect of Social Media Marketing and Word-of-Mouth on Tourist Loyalty: The Mediating Role of Revisit Intention at PT Bali Hai Mandiri Sakti, Bali - Putu Juarez Robin Putra; I Gusti Ngurah Agung Gede Eka Teja Kusuma; I Gusti Ngurah Bagus Gunadi (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2026)
Consumer loyalty reflects customers' commitment to repurchase preferred products or services despite competing alternatives. This study aims to examine the effects of social media marketing and word of mouth on tourist loyalty, with revisit intention serving as a mediating variable at PT. Bali Hai Mandiri Sakti, Bali. The study employed a quantitative approach involving 150 tourists selected using Hair's sampling formula. Data were collected through questionnaires, interviews, and documentation and analyzed using Partial Least Squares (PLS). The findings reveal that social media marketing and word of mouth have positive and significant effects on revisit intention. Both variables also positively and significantly influence tourist loyalty. In addition, revisit intention has a positive and significant effect on tourist loyalty and partially mediates the relationships between social media marketing and tourist loyalty, as well as between word of mouth and tourist loyalty. These findings indicate that effective social media marketing and positive word of mouth enhance tourist loyalty both directly and indirectly by strengthening tourists' intention to reuse the services of PT. Bali Hai Mandiri Sakti. The study highlights the importance of integrating digital marketing and customer recommendations to foster sustainable tourist loyalty.